2012
DOI: 10.1111/j.1365-2710.2012.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Junctional bradycardia with verapamil in renal failure - care required even with mild hyperkalaemia

Abstract: Renal failure patients with baseline mild hyperkalaemia are particularly liable to bradyarrhythmias with SR verapamil. In such cases, we would recommend verapamil dose reduction and avoidance of SR formulation. In cases of verapamil toxicity, actively treating any level of hyperkalaemia is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Although in a rare number of cases, such changes might be absent, but usually the absence of such findings in a patient with hyperkalemia and severe junctional bradycardia favors an additional etiology of the bradycardia. e synergism of hyperkalemia with negative dromotropic agents, resulting in bradycardia, is well defined with multiple case reports highlighting such findings in patients on verapamil [18,19]. We propose that ranolazine can produce a similar effect, thereby leading to a syndrome analogous to BRASH.…”
Section: Discussionmentioning
confidence: 84%
“…Although in a rare number of cases, such changes might be absent, but usually the absence of such findings in a patient with hyperkalemia and severe junctional bradycardia favors an additional etiology of the bradycardia. e synergism of hyperkalemia with negative dromotropic agents, resulting in bradycardia, is well defined with multiple case reports highlighting such findings in patients on verapamil [18,19]. We propose that ranolazine can produce a similar effect, thereby leading to a syndrome analogous to BRASH.…”
Section: Discussionmentioning
confidence: 84%
“…It contains characteristic effects of both hyperkalemia and AV nodal blocker toxicity. Studies have shown that verapamil, a CCB, in the presence of mild hyperkalemia, can accentuate AV conduction delay, leading to junctional bradycardia [3][4]. Thus, significant symptomatic bradycardia can be seen without the typical EKG changes seen in severe hyperkalemia such as a wide QRS or peaked T waves [2].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with BRASH syndrome develop renal failure that leads to hyperkalemia. This has a synergistic effect with AV node blockers, i.e., BB and CCB, with the subsequent development of profound hypotension and bradycardia [3][4]. A key characteristic of BRASH syndrome is mild hyperkalemia causing significant bradycardia without other, typical electrocardiogram (EKG) changes (i.e., widening QRS, peaked T-waves).…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that many clinicians have not clearly mentioned this clinical presentation as BRASH syndrome. Nine cases were identified in seven different studies [2][3][4][5][6][7][8]. The age of presentation ranged between 24 and 97 years with the mean age of 72 years.…”
Section: Discussionmentioning
confidence: 99%